Pengembangan Multimedia Interaktif Keramat (Keragaman Rumah Adat) Berbasis Macromedia Pada Pelajaran IPS Kelas IV Sekolah Dasar - Verdian Lianto Hermansyah; Muhamad Basori; Karimatus Saidah (AL-ASASIYYA: Journal Of Basic Education, 2022)
The purpose of this study was to determine the validity, practicality and effectiveness of development of macromedia-based keramat interactive multimedia (Diversity of Traditional Houses). The results of this study are (1) Macromedia get an average result of 80.5% in terms of media and material validity, which means that macromedia is included in the valid category. (2) Macromedia can be categorized as very practical, this is evidenced by the average response of teachers and students, which is 95.5%. (3) Researchers used pre-test and post-test as a benchmark for assessment. The average pre-test score of students before using macromedia was 74, while the average post-test score of students before using macromedia was 93. The average results of the pre-test to the post-test experienced an increase in the use of Macromedia, which can be declared effective as a learning medium.